Desenvolvimento de um webapp para gerenciamento e monitoramento de terapias-therapy. - LISBOA, Júlio Ramon Nogueira (2020)
The WEB platform underwent many modifications in the last years, its architecture was improved and due to its advances, it was possible to develop more robust softwares, with dimensions of large systems, which was only possible in Desktop systems. Therefore, a new niche emerged: the WebApps. In this sense, this work addresses the development of a system, on the WEB platform, for management and monitoring of therapies. It also describes the agile processes and methodologies adopted for the development of the system, respecting the standards established by the software engineering community. The purpose of Therapy is to organize, manage, record the results of therapies and assist in decision-making through reports generated from a form generator, incorporated into the patient's chart. This form will be created by the system's participating therapists. The chosen technologies and the applied methodology were successful in their objective, so the not contemplated and developed points (reporting and usability tests), were not due to limitations of the methodology or resources of the used technology, but for other reasons (skillful time). Despite the open gaps, the software has great potential for a marketable end product and/or producing other similar jobs.